Early childhood caries in relation to sweet foodstuffs consumption and oral hygiene practices in nursery-age children - Pels, Elżbieta; Tkacz-Ciebiera, Izabela (Journal of Stomatology, 2017)
Introduction. Accurate and regular cleaning of the oral cavity, in conjunction with an anti-caries feeding scheme, is essential to reduce the risk of early childhood caries (ECC). Aim of the study. To evaluate the prevalence of early childhood caries in nurseryage children and to assess the impact of sweets consumption and toothbrushing on the development of early childhood caries. Material and methods. The study comprised 346 children 7 to 48 months of age who were examined clinically. Also the epidemiological study assessed the prevalence of caries and its severity. Results. The frequency of caries in the studied group of children was 44.51%. Statistical analysis showed significantly lower prevalence of caries in the children who did not consume sweets and brushed their teeth than in children, whose teeth were not regularly brushed. Conclusions. The results confirm the need to intensify educational activities involving parents/ carers of young children concerning proper eating habits and hygiene practices since implementation of recommended standards significantly impacts frequency of caries. Early elimination of incorrect eating habits and due respect for the fundamental